2022
DOI: 10.3390/inorganics10060076
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Deficient Ru(II) Complexes as Catalyst Precursors for Ethylene Hydrophenylation

Abstract: Ruthenium(II) complexes with the general formula TpRu(L)(NCMe)Ph (Tp = hydrido(trispyrazolyl)borate, L = CO, PMe3, P(OCH2)3CEt, P(pyr)3, P(OCH2)2(O)CCH3) have previously been shown to catalyze arene alkylation via Ru-mediated arene C–H activation including the conversion of benzene and ethylene to ethylbenzene. Previous studies have suggested that the catalytic performance of these TpRu(II) catalysts increases with reduced electron-density at the Ru center. Herein, three new structurally related Ru(II) complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
2
1
0
Order By: Relevance
“…The energy of methyl acrylate coordination to the phenyl intermediates Int1 formed in the CMD stage changes from −8.1 kcal/mol to +10.6 kcal/mol as the number of carbonyl ligands increases from 1 to 4 in Ru(II) complexes and from 14.2 kcal/mol to 26.9 kcal/mol in Ru(III) mono‐ and di‐carbonyls. It was previously shown that electron‐withdrawing ligands lower the barrier for ethylene insertion into the Ru−phenyl bond [62] . In the present work, we found that electron‐withdrawing carbonyl ligands tend to decrease the height of TS2 but increasing Ru coordination number exerts an opposing effect.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The energy of methyl acrylate coordination to the phenyl intermediates Int1 formed in the CMD stage changes from −8.1 kcal/mol to +10.6 kcal/mol as the number of carbonyl ligands increases from 1 to 4 in Ru(II) complexes and from 14.2 kcal/mol to 26.9 kcal/mol in Ru(III) mono‐ and di‐carbonyls. It was previously shown that electron‐withdrawing ligands lower the barrier for ethylene insertion into the Ru−phenyl bond [62] . In the present work, we found that electron‐withdrawing carbonyl ligands tend to decrease the height of TS2 but increasing Ru coordination number exerts an opposing effect.…”
Section: Resultssupporting
confidence: 63%
“…It was previously shown that electron-withdrawing ligands lower the barrier for ethylene insertion into the RuÀ phenyl bond. [62] In the present work, we found that electron-withdrawing carbonyl ligands tend to decrease the height of TS2 but increasing Ru coordination number exerts an opposing effect. Thus, TS2 changes from 58.1 kcal/mol to 24.8 kcal/mol and on to 25.2 kcal/mol as the number of carbonyl ligands increases from 1 to 3 in Ru(II) complexes and from 35.3 kcal/mol to 20.6 kcal/mol and on to 28.9 kcal/ mol kcal/mol as the number of carbonyl ligands increases from 0 to 2 in their Ru(III) analogs (Table 3).…”
Section: Oxidative Coupling Initiated By Benzene Activationsupporting
confidence: 50%
“…Our group and others have reported catalysts for arene alkylation using molecular Pt, Ru, Ir, , and Ni complexes. , With the exception of the Ni-mediated chemistry, the selectivity for linear alkyl arenes using α-olefins is modest, and, in the case of some Pt catalysts, the arene alkylation reactions are selective for branched products (Scheme ). ,,,, Catalysis based on Ru, Pt, and Ir were proposed to have similar mechanisms that involve olefin insertion into a M–aryl bond, arene coordination, and arene C–H activation to release an alkyl arene product .…”
Section: Introductionmentioning
confidence: 96%